Emotional intelligence and critical thinking for library leaders - Shaffer, Gary L., 1963- (Fundamentals of library management, 2020)
As the use of libraries changes, leaders need to improve their emotional intelligence and critical thinking in order to attract and retain users. Focused on practical management advice, this is an engaging discussion of how library leaders can grow in their role.